Inhalation Therapy for Lung Diseases: A Comprehensive Review of Pulmonary Drug Delivery Systems - Gaurav P.Aswar,; Pooja R. Hatwar,; Dr. Ravindra L. Bakal,; Gopal R.sonone,; Om N.Ajmire, (Asian Journal of Pharmaceutical Research and Development, 2025)
Inhalation therapy has become a popular method for treating respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD). The lungs are the primary organs responsible for gas exchange, and inhalation therapy provides a direct route for drug delivery. Various pulmonary drug delivery systems, including metered-dose inhalers, dry powder inhalers, and nebulizers, have been developed to improve the efficacy of inhalation therapy. These systems utilize various carriers, such as liposomes, nanoparticles, and microspheres, to deliver drugs directly to the lungs, enhancing efficacy and reducing systemic side effects. This review provides a comprehensive overview of the different types of pulmonary drug delivery systems, their advantages and disadvantages, and their applications in treating various lung diseases. The article also discusses the role of nanotechnology in pulmonary drug delivery and the potential benefits of using nanoparticles for targeted drug delivery.